PERLAKUAN AKUNTANSI SETELAH PAJAK TANGGUHAN TERHADAP LAPORAN KEUANGAN PADA PT BEKJORINDO PARYAWEKSANA BANDAR LAMPUNG - Pebrina Swissia (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2016)
Financial statements Bekjorindo Paryaweksana a commercial financial statements in accordance with Financial Accounting Standards (IFRSs) in 2004 while the fiscal financial statements based on the tax rules berlaku.Pada financial statements of PT. Paryaweksana Bekjorindo is unknown pakah company has adopted SFAS no. 46 of 2004 regarding income tax accounting, the accounting treatment after deferred tax is carried out by the company if it is implemented or not and after application of deferred tax if the income earned into small or large.The aim of the event is to demonstrate empirically about the accounting treatment of deferred tax and after the presentation in the financial statements PT.Bekjorindo Paryaweksana Lampung.Method used is quantitative analysis by calculating deferred income taxes according to year-on-year due to the timing differences are that in 2003 there were deferred tax liabilities amounting to Rp. 483,881.00 while in 2004 there were deferred tax assets amounting to Rp. 169,399.00 and in 2005 amounted to Rp. 793,369.00 Keywords: Tax, Deferred Tax, Fiscal